INNOVATIVE APPROACHES TO SUSTAINABLE DEVELOPMENT OF SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP (Marketing Journal, 2025)
this article describes the role of small business and private entrepreneurship in the national economy, its characteristics, factors affecting the development of the sector, the main innovative approaches to the development of the entrepreneurship sector i n our country.
Keywords: small business; entrepreneurship; innovation; innovative approach; technological developments; business environment; economic and social; technological factors; small enterprise; micro -firm